The many shades of digital vigilantism. A typology of online self-justice. Issue 3 (1st October 2020) - Loveluck, Benjamin
ABSTRACT: Digital vigilantism involves direct online actions of targeted surveillance, dissuasion or punishment, which tend to rely on public denunciation or on an excess of unsolicited attention, and are carried out in the name of justice, order or safety. Drawing on a diversity of case studies, this article seeks to provide a comprehensive picture of its manifestations, addressing both the social practices and digital media dynamics involved. It presents a typology which distinguishes between four ideal types of digital vigilantism: flagging, investigating, hounding and organised leaking.